Long term investigation of bonding characteristics between PVC based inhibitor and HTPB/IPDI based propellant - Radulović Jovan; Milojković Aleksandar (Scientific Technical Review)
Bonding characteristics between extruded polyvinyl chloride (PVC) inhibitor and casted hydroxyl terminated polybutadiene/isophorone isocyanate (HTPB/IPDI) propellant, investigated in a long period of time, are topics of this paper. Basic statements about poly(vinyl) chloride, extrusion process and PVC tube (including compound formulation) are presented. There are, also, important considerations about propulsion systems, HTPB/IPDI propellant, plasticizer, casting technology and inhibitor. Specimens for investigation the properties of bond between inhibitor and external radial surface of solid propellant and specimens for determining the characteristics of bond between inhibitor and flat surface of solid propellant are shown. Two kinds of characteristics of bond between PVC based inhibitor and external radial surface HTPB/IPDI based propellant were examined: strength properties and visual appearance. Strength characteristics include arithmetic mean value of bond strength and arithmetic mean value and standard deviation of bond strength. Mentioned properties, as indication of quantitative aspects of tested bond, were obtained using appropriate method of determination and specific tool, adjusted to geometry of propellant. Visual appearance of separated PVC parts and of remaining of PVC inhibitor-HTPB/IPDI propellant specimens, as indication of qualitative aspects of tested bond, were tested visually. Based on visual appearance of mentioned separated parts an assessment of way of separation was done. Strength characteristic of PVC inhibitor-HTPB/IPDI propellant specimens and visual appearance of separated parts were determined at the start of investigation procedure, after five years of ageing and after eleven years of weathering in warehouse conditions. Both mentioned properties were tested at temperature 20 oS and temperature 50 oS. Data obtained by testing PVC inhibitor-HTPB/IPDI propellant specimens are presented in Tables and in Figures.